Pengaruh Digital Marketing dan E-Wom (Elektronic Word of Mouth) terhadap Keputusan Pembelian di Shopee - Roni Iskandar; Moh. Kurdi (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2024)
This research aims to investigate the influence of digital marketing and e-Wom (electronic word-of-mouth) on purchasing decisions on the Shopee e-commerce platform. The online survey method was used to collect data from 115 respondents who were active Shopee users. The results of multiple linear regression analysis show that digital marketing and e-Wom have a positive and significant influence on purchasing decisions at Shopee. These findings show the importance of effective digital marketing strategies and e-Wom drivers in improving consumer purchasing decisions in the e-commerce era. The practical and theoretical implications of these findings are discussed in the context of digital marketing strategies and customer relationship management on e-commerce platforms.